Detection of campylobacter in gastroenteritis: comparison of direct PCR assay of faecal samples with selective culture. - Lawson, A. J. (Cambridge University Press, 1998)
The prevalence of campylobacter gastroenteritis has been estimated by bacterial isolation using selective culture. However, there is evidence that certain species and strains are not recovered on selective agars. We have therefore compared direct PCR assays of faecal samples with campylobacter culture, and explored the potential of PCR for simultaneous detection and identification to the species level. Two hundred unselected faecal samples from cases of acute gastroenteritis were cultured on modified charcoal cefoperazone deoxycholate agar and subjected to DNA extraction and PCR assay. Culture on CCDA indicated that 16 of the 200 samples contained 'Campylobacter spp.'. By contrast, PCR assays detected campylobacters in 19 of the 200 samples, including 15 of the culture-positive samples, and further identified them as: C. jejuni (16), C. coli (2) and C. hyointestinalis (1). These results show that PCR offers a different perspective on the incidence and identity of campylobacters in human gastroenteritis.